Pengaruh Kontrol Diri terhadap Kedisiplinan pada Siswa Kelas X SMK Pasundan Jatinangor - Pebrian, Rio; Rachmaniar, Ananda; Rayaginansih, Syari Fitrah (Jurnal Dimamu, 2025)
This study aims to examine the effect of self-control on student discipline at SMK Pasundan Jatinangor. A quantitative approach employing a survey method was utilized. The sample consisted of 235 tenth-grade students, selected using a saturated sampling technique. Data analysis using simple linear regression revealed that self-control has a positive and significant effect on student discipline. The regression coefficient value of 1.099 with a significance level of 0.000 (< 0.05) indicates that each increase in self-control is followed by an increase in student discipline. The coefficient of determination (R Square) value of 0.589 shows that self-control contributes 58.9% to student discipline, while the remaining 41.1% is influenced by other variables not examined in this study. The categorization results also indicate that the majority of students fall into the high self-control and high discipline categories. These findings highlight the importance of fostering self-control as a strategy to enhance student discipline, both in academic contexts and in overall school setting.